Stroke and brain atrophy in chronic Chagas disease patients: A new theory proposition - Jamary Oliveira-Filho (Dementia & Neuropsychologia)
Abstract Chagas disease (CD) remains a major cause of cardiomyopathy and stroke in developing countries. Brain damage in CD has been attributed exclusively to the effects of structural heart disease on the brain, including cardioembolism and low cardiac output symptoms. However, CD patients also develop stroke and brain atrophy independently of cardiac disease severity. Chronic inflammation directed against T. cruzi may act as a trigger for endothelial damage, platelet activation, acceleration of atherosclerosis and apoptosis, all of which lead to stroke and brain atrophy. In the present article, evidence supporting this new theory is presented, along with considerations towards mechanistically-based targeted treatment.